1998
DOI: 10.1097/00004872-199816060-00017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of interindividual variation of renin and prorenin concentrations

Abstract: These data demonstrate that there is a sexual dimorphism of prorenin levels in humans, suggesting that sex hormones affect the regulation of the renin gene. Data confirm previous reports of elevated prorenin levels in diabetics and older subjects, as well as of lower than normal prorenin levels in subjects with hypertension in smaller populations. Our findings may help to clarify the potential (patho)physiologic functions of prorenin and to identify the factors that influence the constitutive secretion and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
136
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(149 citation statements)
references
References 30 publications
12
136
1
Order By: Relevance
“…Alge et al (4) recently reported that urinary renin, together with urinary angiotensinogen, associates with AKI after cardiac surgery. Their urinary renin levels were measured with the Quantikine Renin ELISA Kit and exceeded published plasma renin levels (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alge et al (4) recently reported that urinary renin, together with urinary angiotensinogen, associates with AKI after cardiac surgery. Their urinary renin levels were measured with the Quantikine Renin ELISA Kit and exceeded published plasma renin levels (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the kit simultaneously detects both renin and prorenin, and thus, given that in most body fluids prorenin greatly exceeds renin (up to 100-fold), it provides information on prorenin (11,12,16). Remarkably for a renin kit, the ELISA uses recombinant prorenin as a standard, and even more concerning, this prorenin has not been calibrated against the International Reference Preparation of human renin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of aliskiren to inhibit prorenin activation has additional relevance because circulating levels of prorenin are about 10-fold those of renin. 125 This represents high potential renin activity. In addition, plasma prorenin levels can be substantially elevated in diabetes 126 and are strongly associated with microvascular complications of this disease.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 98%
“…Renin may diffuse into the interstitial space (18,28) or bind to renin receptors and/or renin-binding proteins (8,46,53). Because renin in blood is predominantly present in the form of its inactive precursor prorenin (11), it is also conceivable that the heart sequesters prorenin instead of renin. This prorenin must then be activated locally.…”
mentioning
confidence: 99%